The Effectiveness of Fish Oil and Ginger Drink in Reducing Dysmenorrhea: A Meta Analysis - Novitasari, Isnaini; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Dysmenorrhea causes 34-50% of women to be unable to work in the workplace and 40% of adolescent girls are absent from school. Fish oil and ginger are used as alternatives to NSAIDs, because although the use of NSAIDs is effective in reducing dysmenorrhea pain, they have side effects that are harmful to health after long-term conventional therapy. This study aims to estimate the magnitude of the effect of fish oil and ginger in reducing dysmenorrhea in women of reproductive age. Subjects and Method: This was a meta-analysis and systematic study. The articles used were obtained from PubMed, Science Direct, ProQuest, Springer Link, and Google Scholar. The inclusion criteria used were full text articles with Randomized Control Trial (RCT). The study subjects are women of productive age. The treatment given was the consumption of fish oil or ginger with a placebo comparison, dysmenorrhea assessment using standardized measuring instruments such as VAS, Cox, questionnaires, etc. Articles published in English. The PICO Research Problem are population= women of reproductive age, intervention= fish oil or ginger, comparison= placebo, and outcome= dysmenorrhea. The study was assessed using an effect size (Standardized Mean Difference). Meta analysis was performed using RevMan 5.3 with Random Effect Model. Results: A total of 14 articles were reviewed in a meta-analysis in this study. Meta-analysis of 6 articles showed that fish oil reduced dysmenorrhea pain in women of reproductive age higher than placebo (Standardized Mean Difference= -1.06; 95% CI= -1.76 to -0.36; p= 0.003). Meta-analysis of 8 articles showed that ginger reduced dysmenorrhea pain in women of childbearing age more than placebo (Standardized Mean Difference= -0.77; 95% CI= -1.26 to -0.27; p=0.002). Conclusion: Fish oil and ginger are effective in reducing dysmenorrhea pain in women of reproductive age.